A Motor Speech Assessment for Children With Severe Speech Disorders: Reliability and Validity Evidence. - Strand, Edythe A.; McCauley, Rebecca J.; Weigand, Stephen D.; Stoeckel, Ruth E.; Baas, Becky S.; Kreiman, Jody; Liss, Julie (Journal of Speech, Language & Hearing Research, 2013)
Purpose: In this article, the authors report reliability and validity evidence for the Dynamic Evaluation of Motor Speech Skill (DEMSS), a new test that uses dynamic assessment to aid in the differential diagnosis of childhood apraxia of speech (CAS). Method: Participants were 81 children between 36 and 79 months of age who were referred to the Mayo Clinic for diagnosis of speech sound disorders. Children were given the DEMSS and a standard speech and language test battery as part of routine evaluations. Subsequently, intrajudge, interjudge, and test-retest reliability were evaluated for a subset of participants. Construct validity was explored for all 81 participants through the use of agglomerative cluster analysis, sensitivity measures, and likelihood ratios. Results: The mean percentage of agreement for 171 judgments was 89% for test-retest reliability, 89% for intrajudge reliability, and 91 % for interjudge reliability. Agglomerative hierarchical cluster analysis showed that total DEMSS scores largely differentiated clusters of children with CAS vs. mild CAS vs. other speech disorders. Positive and negative likelihood ratios and measures of sensitivity and specificity suggested that the DEMSS does not overdiagnose CAS but sometimes fails to identify children with CAS. Conclusions: The value of the DEMSS in differential diagnosis of severe speech impairments was supported on the basis of evidence of reliability and validity.